صحابیات کے اسلوبِ دعوت و تربیت کی روشنی میں پاکستانی خواتین کی کردار سازی: Character-building of Pakistani Women in the light of Daʻwah and Training Styles of Saḥābiyāt (Al-Qamar, 2022)
This article deals with character-building of Pakistani women in the light of the style of Dawa’h and training of Saḥābiyāt. It argues that male and female Companions of the Prophet of Islam always kept in mind the guidance and behavior of the Messenger of Allah, in Dawa’h and preaching. In the present era many Muslim men and women are doing Dawa’h and Tablāgh. Women are contributing a lot in this field, but the method of the contemporary women mostly   are unfamiliar with the methodology of Saḥābiyāt in this regard. This research maintains that it is very important for Dawa’h workers to be well aware of the requirements of the modern age and the resources available in the field. This paper concludes that today’s women should follow the examples of Saḥābiāt in the field of Dawa’h specially the example of Hazrat Ayisha Siddiqa.
Keywords: Saḥābiyāt; Dawa’h; Character-building; women; Pakistan